The Effect of the Polymorphism on the 5\' Region of the Leptin gene (G2548A) on the Possibility of Breast Cancer in two Studies Groups - zahra Tahmasebi Fard (Fasa University of Medical Sciences, 2019)
Background & Objective: Leptin a hormone secreted from adipose tissue plays a role in regulating energy homeostasis. Polymorphism in the gene structure can alter serum levels of hormone and affect cell function. In this study, the relationship between G2548A polymorphism of the leptin gene with the risk of breast cancer in patients compared with healthy subjects was investigated. Materials and Methods: The blood sample of 158 women with breast cancer and 158 healthy women of the same age was collected and after extracting DNA and amplifying specimens with specific primers, some part of products was digested with HhaI restriction enzyme to determine the genotypes of individuals based on the number of bands formed on the gel. The results were analyzed by statistical analysis including chi-square, and logistic regression. Results: The mean age of the patients was 56.00±0.62 years old and the control groups was 55.45±0.72 years old (p-value =0.037). There was a significant relationship between the smoking level of the two groups (p-value =0.026). The history of relatives of breast cancer patients was positive in 43 (27.22%) patients. Analysis of the results of genotypes showed that the mutant homozygote genotype AA had a significant relationship in two groups and increased by 1.686 the risk of breast cancer (P-Value=0.036, OR:1.686, CI95%:1.033-2.753). Conclusion: The frequency of mutant A allele in the patient group was more than that of the control groups and increased the risk of breast cancer by 1.763 times in carriers. Overall, it can be said that this polymorphism is probably related to breast cancer.